2002
DOI: 10.1086/341920
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Cefoxitin‐ResistantBacteroides thetaiotaomicronMutants and Mechanisms Involved in β‐Lactam Resistance

Abstract: The beta-lactam antibiotics are the most widely used of all the groups of antimicrobials, but beta-lactam resistance is increasingly common among members of the Bacteroides fragilis group. Three major mechanisms are involved in beta-lactam resistance, and they act together in certain instances. In the present study, 2 resistant mutants (238m and 1186m) of Bacteroides thetaiotaomicron, obtained from clinical isolates (238 and 1186) by selection with increasing concentrations of cefoxitin, showed decreased susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…Resistance to ␤-lactams in anaerobic bacteria is attributed primarily to the constitutive production of high levels of ␤-lactamase (10). In a recent in vitro study, it was demonstrated that resistant Bacteroides strains selected with the cephalosporin cefoxitin displayed no enhanced ␤-lactamase activity compared to that of the parent strain but did have altered penicillin-binding proteins and outer membrane proteins (14). In addition, this resistance was lost after multiple subcultures on antibiotic-free agar, indicating that the alterations were only produced under antibiotic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to ␤-lactams in anaerobic bacteria is attributed primarily to the constitutive production of high levels of ␤-lactamase (10). In a recent in vitro study, it was demonstrated that resistant Bacteroides strains selected with the cephalosporin cefoxitin displayed no enhanced ␤-lactamase activity compared to that of the parent strain but did have altered penicillin-binding proteins and outer membrane proteins (14). In addition, this resistance was lost after multiple subcultures on antibiotic-free agar, indicating that the alterations were only produced under antibiotic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Expandedspectrum cephalosporins are more likely to select resistant strains of Enterobacteriaceae than are other ␤-lactams (23,30,35), while piperacillin (PIP)-tazobactam (TAZ) (the combination of PIP and TAZ is abbreviated PT) appears to suppress the selection of derepressed mutants (20). Very little data are available on the selection of ␤-lactam resistance in B. fragilis strains (10,14,18,37).…”
mentioning
confidence: 99%
“…Alterations in PBPs, mainly changes in PBP1 and/or PBP2, have been implicated in non-␤-lactamase-mediated cefoxitin resistance in cefoxitin-resistant mutants of B. fragilis group species (187,298). The affinities of the PBP1 complex (86 kDa) of B. thetaiotaomicron 238m for cefoxitin and piperacillin were Ͼ100-fold and ϳ70-fold reduced, respectively, compared with those of its parent strain (85). The ortholog of the E. coli PBP3 gene (pbpBBfr, which encodes the protein PBP2Bfr) was implicated in binding to imipenem (6,188).…”
Section: Mechanisms Of Antimicrobial Resistancementioning
confidence: 99%
“…Altered PBP 2 or PBP 1 complexes have been reported in rare clinical isolates, resulting in cefoxitin and other cephalosporin resistance in B. fragilis [30], or can be induced in vitro [31]. A third mechanism of resistance is the most recent to be studied and perhaps the least understood.…”
Section: Trends and Mechanisms Of Antibiotic Resistance Among Anaerobmentioning
confidence: 99%